Pengaruh Laba per Saham, Rasio Hutang dan Pengembalian atas Aset (ROA) terhadap Harga Saham: Studi Kasus pada Perusahaan Pertambangan - Jocelyn Govia; Venita Ozty Susan Dayani; Mohd. Nawi Purba; Enggolit Ramayanti; Michael Tanoto; Sauh Hwee Teng; Cynthia Cynthia (Politeknik Ganesha Medan, 2019)
The purpose of this research is to examine the influence of earning per share, debt to equity ratio, and return on assets (ROA) to stock price. This research was conducted on mining companies listed in Indonesia Stock Exchange period 2012-2017. The analysis method used is multiple linear regression analysis, F test and T test. The analysis result of this research shows that stock price is influenced simultaneously by earning per share, debt to equity ratio, and return on assets (ROA). Meanwhile, the partial analysis shows that earning per share influences significantly on stock price, debt to equity ratio influences but insignificantly on stock price, and return on assets (ROA) doesn’t influence but is significant on the stock price.